2015
DOI: 10.1109/mprv.2015.65
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Motivations for Using Grocery Shopping Applications

Abstract: For more than two decades, researchers have been investigating how to technologically enhance the in-store shopping experience. 1 The focus has mainly been on applying shopping assistants at the point of sale, 1-5 but users employ multiple types of devices in multiple contexts and locations, not only in stores. 6 More research is thus needed to understand users' motivations for using shopping applications in the first place.To explore such motivations, we studied the use of Foodie. fi, a popular grocery shoppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[128][129][130][131][132][133][134][135][136] Accessibility A total of 48 studies (13%) related to the accessibility dimension as defined in the food environment framework used. These studies, mostly based on consumer perceptions, 42,[74][75][76][77][78][79][80]104,106,[109][110][111][137][138][139][140][141][142][143][144][145][146][147] indicate that food accessibility in the digital food environment relates mostly to time used to acquire food when buying groceries online or ordering food delivery services, as well as the transportation needs to access these foods. Only two studies 138,148 investigated the actual time used for buying food online or changes in travel habits.…”
Section: Personal Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…[128][129][130][131][132][133][134][135][136] Accessibility A total of 48 studies (13%) related to the accessibility dimension as defined in the food environment framework used. These studies, mostly based on consumer perceptions, 42,[74][75][76][77][78][79][80]104,106,[109][110][111][137][138][139][140][141][142][143][144][145][146][147] indicate that food accessibility in the digital food environment relates mostly to time used to acquire food when buying groceries online or ordering food delivery services, as well as the transportation needs to access these foods. Only two studies 138,148 investigated the actual time used for buying food online or changes in travel habits.…”
Section: Personal Domainmentioning
confidence: 99%
“…While no studies investigated convenience in depth, the existing studies indicated that convenience in the digital food environment can be influenced by food delivery apps that reduce or eliminate time preparing and cooking food, 100,153 by the improved meal planning afforded by food recipe websites and apps, 154 and online grocery shopping. 43,44,77,112,126,145,155,156…”
Section: Affordabilitymentioning
confidence: 99%
“…Over the last decade, HCI has increasingly engaged with food and the potential for digital technology to play a role in its production and consumption [17]. Researchers have designed and studied ICT that shapes how we produce (predominantly through growing of vegetables in community gardens) [42,54,62,78], shop [14,15,45,75], prepare [16,32], eat [1,13,14,18], share [34,36], and dispose of [3,19,30,33] food. Within this, HCI has historically focused on the household level [18,35], with the community level primarily researched through community gardening and urban agriculture studies [54,78].…”
Section: Related Workmentioning
confidence: 99%
“…They conclude that food shopping, cooking, eating and associated waste are socially situated and that the complex circumstances of people's lives and their food practices are intertwined and this needs to be considered in future HCI work. Tukkinen and Lindqvist [2015] explore the real world deployment of a grocery shopping app in Finland, while Abbar, Mejova and Weber [2015] use the Twittersphere to uncover food consumption practices and in particular health impacts of different food choices.…”
Section: Related Workmentioning
confidence: 99%